Dog Man : Guide to Creating Comics in 3-D - Pilky, Dav (New York Scholastic Inc., 2019)
George and Harold know a LOT about making comic books. (Remember their Captain Underpants comics?) But before they told you that story, first they told you the story of Dog Man -- part dog, part man, and all cop! Want to know how George and Harold come up with hilarious heroes like Dog Man and Li'l Petey and Chief? And how do they think up such wretched villains, like Petey and Piggy and Philly? Now's your chance to find out! The boys will give step-by-step instructions on how to draw some of their best Dog Man characters. Plus, get advice on how to create your own funny comic-book characters -- and bring them to life in 3-D!
Include Color Illustrations
Keywords: Comic books, strips, etc -- Technique -- Juvenile literature. -- Comic books, strips, etc. -- Technique